Few-Layered Fluorinated Triazine-Based Covalent Organic Nanosheets for High-Performance Alkali Organic Batteries - Zhang, Hang; Sun, Weiwei; Chen, Xiudong; Wang, Yong (ACS nano, 2019)
In order to fulfill the increasing demand for renewable energy, besides the lithium-ion batteries, other alkali (Na, K)-ion batteries are extensively investigated. However, the difficulty to find universal and environmentally benign electrodes for these alkali (Na, K)-ion batteries still severely restricts their development. Promising characteristics, including molecular diversity, low cost, and operation safety, endow the organic electrodes more advantages for applications in alkali-ion batteries. However, organic electrodes usually deliver a reversible capacity smaller than that of their inorganic counterparts due to sluggish ion/electron diffusion and possible dissolution in organic electrolytes. This work introduces fluorine atoms into the covalent triazine frameworks (CTF) to obtain two-dimensional layered fluorinated CTF (FCTF) and its exfoliated few-layered product (E-FCTF) and uses them as anodes of Li, Na, and K organic batteries. Exfoliated E-FCTF electrode delivers high reversible capacities, as well as excellent cycle life for alkali organic batteries (1035 mAh g–1 at 100 mA g–1 after 300 cycles and 581 mAh g–1 at 2 A g–1 after 1000 cycles for lithium organic batteries). In view of the experimental probing and the theoretical calculation, the Li storage mechanism for the E-FCTF can be determined to be an intriguing multielectronic redox reaction originated from lithium storage on the benzene ring and triazine ring units.